P93 Social risk factors associated with tuberculosis in a high incidence area of the UK. (14th November 2013) - Ricketts, WM; Anderson, LF; White, VLC
Abstract : Introduction: The London Borough of Newham consistently has the highest incidence of tuberculosis (TB) in the UK (≈120/100, 000), with case numbers continuing to rise. We sought to investigate social risk factors for TB as compared with the general population in this borough. Methods: Of 242 adult patients diagnosed with TB in 2012 at the Newham Chest Clinic 170 (70.3%) completed a structured interview assessing for social risk factors. Demographic data was obtained from hospital records. TB case data was compared with 2011 census data using Fisher's exact test or t-tests as appropriate. Results: Data directly comparable to 2011 census data is summarised in Table 1 . Cases had a mean of 3.43 (95% CI 3.07–3.8) household contacts, 2.28 (1.41–3.16) non-household family contacts and 2.02 (1.71–2.33) close friends. Household and family contacts were almost exclusively of the same ethnicity as the cases, but with 18.4% of household contacts and 49.2% of family contacts being UK born, compared with 7.7% of cases. The majority of friends were of the same ethnicity (86%) with 18.4% UK born, 89.4% of cases had no close friends from a different ethnic group. None of the cohort reported alcohol or drug abuse or had been in prison in the last 5 years, one was currently homeless. Fifteen (8.8%) reported recent visitors from abroad and 61 (38.9% of foreign born) reported returning to their country of birth for greater than three weeks, with 75.4% having returned within the last two years, a further eleven had travelled to a high incidence country in the last ten years, six of whom were UK born travelling to their parents' country of birth. Conclusions In this high incidence area of an otherwise low incidence country TB is significantly more common in those of South-Asian birth and ethnicity. It is more common in young adults who have lived in the UK between two and five years and work in unskilled jobs or are unemployed. This picture is likely driven by TB reactivation in new immigrants accompanied by a lack of social mixing and suggesting the influence of relative poverty in the development of TB.